Insectary production and synopsis of Fopius caudatus (Hymenoptera: Braconidae), parasitoid of tephritid fruit ﬂies indigenous to Africa - BOKONON GANTA, AIME H; RAMADAN, MOHSEN M; MESSING, RUSSELL H (My University, 2019)
Fopius caudatus (Szépligeti) is an endophagous koinobiont egg-larval parasitoid native to Africa. It has recently been noted as a candidate for augmentative biological control of several Dacinae fruit ﬂy pests (Diptera: Tephritidae), due to its ability to parasitize the egg stage. Previous attempts to establish this parasitoid in Hawaii, Guatemala, and Costa Rica were unsuccessful due to inability to maintain parasitoid colonies under laboratory conditions. A cohort of F. caudatus collected from Kenyan fruit ﬂies infesting Coﬀea arabica was successfully colonized in Hawaii at 28 °C and 60–80% RH, resulting in the development of a laboratory-adapted colony amenable for mass production. The parasitoid was successfully developed from eggs of Ceratitis capitata and Bactrocera latifrons as a factitious host. The wasps were propagated for 15 weeks until the rearing stabilized, at which point > 10,500 adults were produced with an overall sex ratio of 0.52 females and a mean host parasitism rate of 17.3%. It could parasitize Medﬂy eggs in fruits other than coﬀee, including papaya, mango, pear, squash, and sweet pepper. Female F. caudatus oviposited mainly in 24–48 h old Medﬂy eggs, although occasionally a few individuals eclosed when ﬁrst instar ﬂy larvae were exposed. Mean developmental time from egg to adult was 19.8 d for males and 21.5 d for females. Mean longevity was 5.2 d for males and 14.2 d for host- deprived females. This study enabled us to maintain a colony of F. caudatus for research and redistribution to other countries for biocontrol programs against Medﬂy.
Keywords: Fopius caudatus Medﬂy Tephritidae Opiinae; biological control; Ceratitis